Respuesta :
Hey!
--------------------------------
Lets try -10:
2(3(-10) - 1) = 4(-10) - 6
2(-30 - 1) = (-40) - 6
2(-31) = (-40) - 6
-62 ≠ -46
Incorrect.
--------------------------------
Lets try -5:
2(3(-5) - 1) = 4(-5) - 6
2(-15 - 1) = (-20) - 6
2(-16) = (-20) - 6
-32 ≠ -26
Incorrect.
--------------------------------
Lets try -3:
2(3(-3) - 1) = 4(-3) - 6
2(-9 - 1) = (-12) - 6
2(-10) = (-12) - 6
-20 ≠ -18
Incorrect.
--------------------------------
Lets try -1:
2(3(-1) - 1) = 4(-1) - 6
2(-3 - 1) = (-4) - 6
2(-4) = (-4) - 6
-8 ≠ -10
Incorrect.
--------------------------------
So all the options are incorrect.
--------------------------------
Lets solve for x:
2(3x - 1) = 4x - 6
(2 * 3x) + (2 * -1) = 4x + (-6)
6x + (-2) = 4x + (-6)
6x - 2 = 4x - 6
6x - 2 - 4x = 4x - 6 - 4x
2x - 2 = -6
2x + 2 - 2 = -6 + 2
2x = -4
2x/2 = -4/2
x = -2
--------------------------------
Hope This Helped! Good Luck!